Feasibility of a novel mixed-nutrient supplement in a multimodal prehabilitation intervention for lung cancer patients awaiting surgery: A randomized controlled pilot trial. (September 2021) - Ferreira, Vanessa; Lawson, Claire; Carli, Francesco; Scheede-Bergdahl, Celena; Chevalier, Stéphanie
Abstract: Objective: To investigate, in lung cancer patients awaiting elective surgery, the feasibility of delivering a novel four-week multimodal prehabilitation intervention and its effects on preoperative functional capacity and health-related quality of life (HRQoL), compared to standard hospital care. Methods: Adult patients awaiting elective thoracotomy for lung cancer stages I, II or IIIa, were approached to participate in an open-label, randomized controlled trial of two parallel arms: multimodal prehabilitation combining a mixed-nutrient supplement with structured supervised and home-based exercise training, and relaxation-strategies (Prehab) or standard hospital care (Control). Feasibility was assessed based on recruitment and adherence rates to the intervention and study outcome assessment. Functional capacity, measured by the 6-min walk test (6MWT), and HRQoL were measured at baseline and after four weeks (preoperative). Results: Within 5 months, 34 patients were enrolled and randomized (2:1) to Prehab (n = 24; median age = 67 years) or Control (n = 10; median age = 69 years); recruitment rate of 58.6%. The study was interrupted by the COVID-19 pandemic. Adherence to the prescribed intensity of the supervised exercise program was 84.1% (SD 23.1). Self-reported adherence to the home-based exercise program was 88.2% (SD 21) and to the nutritional supplement, 93.2% (SD 14.2). Adherence to patients' preoperative assessment was 82% and 88% in Prehab and Control, respectively. The mean adjusted difference in 4-week preoperative 6MWT between groups was 37.7 m (95% CI, −6.1 to 81.4), p = 0.089. There were no differences in HRQoL between groups. Conclusion: Within a preoperative timeframe, it was feasible to deliver this novel multimodal prehabilitation intervention in lung cancer patients awaiting surgery. Highlights: Improving functional capacity prior to surgery (prehabilitation) may help recovery. Multimodal prehabilitation combined nutrition, exercise and relaxation strategies. A mixed-nutrient supplement targeting muscle health was well accepted. Multimodal prehabilitation proved feasible in lung cancer patients awaiting surgery.